Embedment of HA/Ti composite on superplastic titanium alloy (Ti-6Al-4V) - Mohamad Dom, Adibah Haneem; Jauhari, Iswadi; Yazdanparast, Sanaz; Mohd Khalid, Hidayah (Elsevier, 2010)
In this research, embedment of HA-2 wt.% Ti composite powder on superplastic Ti-6Al-4V was conducted through continuous pressing technique to improve the low strength of the conventional pure HA coatings. The embedment process was carried out at temperature below the allographic temperature. The bond strength evaluation of HA-2 wt.% Ti composite layer was performed using wear test method under different applied pressure. The experimental results indicated that the HA-2 wt.% Ti composite layer had uniform thickness and well bonded to the substrate. EDX and line scanning analysis revealed that HA elements were detected at the substrate indicating embedment process was successful. The wear test results proved that the strength of the embedded layer on the superplastic Ti-6Al-4V was much better than the as-received Ti-6Al-4V. (C) 2010 Elsevier B.V. All rights reserved.